2001
DOI: 10.1002/rmv.314
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of arboviruses and antiviral antibodies in vertebrate hosts: its occurrence and impacts†

Abstract: The recent isolation of West Nile virus from a bird in mid-winter in New York immediately raised, as one of a few explanations, the possibility of long-term persistence of arboviruses in vertebrate hosts. Although it was a highly popular topic for research many years ago, generally it has since been neglected and its meaning under appreciated. This comprehensive survey of literature worldwide uncovered, contrary to the general perception that it is a rather infrequent phenomenon, a large number of important ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 138 publications
0
74
0
1
Order By: Relevance
“…This is consistent with previous studies that have found IgM antibodies may not develop after secondary flavivirus infections, or may develop more slowly or persist for a shorter period of time when compared with primary infections. [13][14][15] There are several possible explanations for the presence of YF IgM antibodies in the serum of persons 3-4 years postvaccination. First, persistent infection with YF vaccine virus may have resulted in prolonged IgM antibody synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with previous studies that have found IgM antibodies may not develop after secondary flavivirus infections, or may develop more slowly or persist for a shorter period of time when compared with primary infections. [13][14][15] There are several possible explanations for the presence of YF IgM antibodies in the serum of persons 3-4 years postvaccination. First, persistent infection with YF vaccine virus may have resulted in prolonged IgM antibody synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The related WEEV has been found to persist in brain, blood, lung, liver, spleen, and gall bladder tissue of birds for up to 10 months after infection (Reeves et al, 1958;Reisen et al, 2001). Maintenance of chronic virus infections frequently occurs in vertebrates (Kuno, 2001). Relapse of latent virus infection may account for arbovirus overwintering and local persistence of infection among vertebrates within a transmission focus, a scenario well suited for the sedentary house sparrows that live in or near cliff swallow colonies.…”
Section: Detection Of Bcrv In Tissuementioning
confidence: 99%
“…Therefore, a thorough understanding of immune dynamics is essential for accurate serologic interpretation. The half-lives of detectable arboviral antibody responses in birds appear to be shorter than those of mammals (Stamm 1966;Kuno 2001). In avian hosts, following primary infection, antibody levels peak for several weeks, plateau for several months, and then gradually decline (Stamm 1966;Kuno 2001;Ringia et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Birds that survive WNV infection develop antibodies that help protect against subsequent infection (Komar et al 2003;Nemeth et al 2009). However, there appears to be considerable variation in the nature and duration of avian immune responses to arboviruses among individuals and populations (Main et al 1988;Kuno 2001;Reisen et al 2001;Reisen et al 2004;Davison et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation